2019
DOI: 10.1097/ncm.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

Health Coaching for Patients With Type 2 Diabetes Mellitus to Decrease 30-Day Hospital Readmissions

Abstract: Purpose/Objectives: The purpose of this program was to provide health coaching to patients with a primary or secondary diagnosis of Type 2 diabetes mellitus (T2DM) to increase self-management skills and reduce 30-day readmissions. Primary Practice Setting: The setting was a 273-bed, acute care not-for-profit hospital in the southern region of the United States. Findings/Conclusions: Health coaching that emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 6 publications
0
17
1
4
Order By: Relevance
“…Quanto ao cargo ou função do enfermeiro que utilizou Coaching, identifica-se em 48% dos artigos (n=16) enfermeiros assistenciais (Sullivan, et al, 2019;Rahn, et al, 2018;Petursdottir, et al, 2019;Hazard, et al, 2018;Berger-Höger, Liethmann, Mühlhauser & Steckelberg, 2017;Early, et al, 2017;Sherry, et al, 2017;Gray-Miceli, et al, 2017;Cooper & Zimmerman, 2016;Janice, Karen, Justine, Sonya & Genevieve, 2015;Bakitas, et al, 2015), 27% (n=8) o enfermeiro pesquisador (Rocha, et al, 2019;Tweedie, et al, 2019;Miyamoto, et al, 2019;Petursdottir, et al, 2019;Berry, et al, 2015), 6% (n=2) de enfermeiros gerentes (Hazard, et al, 2018;, 6% (n=2) de enfermeiros externos (Ouden, et al, 2019;Nyamathi, et al, 2015) e 6% (n=2) enfermeiros de prática avançada Dionne-Odom, et al, 2015), e enfermeiro docente (Ubolrat, et al, 2015) e enfermeiro intervencionista em 3% (n=1) dos artigos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Quanto ao cargo ou função do enfermeiro que utilizou Coaching, identifica-se em 48% dos artigos (n=16) enfermeiros assistenciais (Sullivan, et al, 2019;Rahn, et al, 2018;Petursdottir, et al, 2019;Hazard, et al, 2018;Berger-Höger, Liethmann, Mühlhauser & Steckelberg, 2017;Early, et al, 2017;Sherry, et al, 2017;Gray-Miceli, et al, 2017;Cooper & Zimmerman, 2016;Janice, Karen, Justine, Sonya & Genevieve, 2015;Bakitas, et al, 2015), 27% (n=8) o enfermeiro pesquisador (Rocha, et al, 2019;Tweedie, et al, 2019;Miyamoto, et al, 2019;Petursdottir, et al, 2019;Berry, et al, 2015), 6% (n=2) de enfermeiros gerentes (Hazard, et al, 2018;, 6% (n=2) de enfermeiros externos (Ouden, et al, 2019;Nyamathi, et al, 2015) e 6% (n=2) enfermeiros de prática avançada Dionne-Odom, et al, 2015), e enfermeiro docente (Ubolrat, et al, 2015) e enfermeiro intervencionista em 3% (n=1) dos artigos.…”
Section: Resultsunclassified
“…Quanto ao tipo de treinamento dos enfermeiros no papel de coach, 36% (n=12) dos artigos não descrevem (Piamjariyakul, et al, 2019;Petty & Lingham, 2019;Noh & Kim, 2019;Petursdottir, et al, 2019;Sherry, et al, 2017;Westland, et al, 2017;Ubolrat, et al, 2015;Berry, et al, 2015;Nyamathi, et al, 2015), 30% (n=10) sinalizam oficinas, workshops, cursos ou treinamentos com textos e vídeos (Tweedie, et al, 2019;Rahn, et al, 2018;Zhang, et al, 2017;Gray-Miceli, et al, 2017;Cooper & Zimmerman, 2016;Janice, et al, 2015;Thoonsen, et al, 2015;Bakitas, et al, 2015;Dionne-Odom, et al, 2015) e 27% (n=9) artigos informa treinamento na ferramenta, técnica ou protocolo aplicado (Sullivan, et al, 2019;Ouden, et al, 2019;Hazard, et al, 2018;Berger-Höger, et al, 2017;Early, et al, 2017; e 6% (n=2) sinalizam formação certificada em Coaching (Rocha, et al, 2019;Miyamoto, et al, 2019).…”
Section: Resultsunclassified
“…Previous studies indicated that patients with cardiac conditions or diabetes with poor self-management behavior had significantly higher readmissions (Topaz et al, 2016;Sullivan, Hays, & Alexander, 2019). Hamar et al (2013) found that chronic disease management programs successfully reduced readmission rates and LOS among patients with heart disease or diabetes.…”
Section: Author Manuscriptmentioning
confidence: 98%
“…Intensive self‐management is the optimal method of achieving glycemic targets and preventing short‐ and long‐term diabetes‐related complications (Powers et al, 2017). However, this complex treatment regimen is difficult to maintain and requires high levels of continuity of care, frequent access to and collaboration with healthcare providers, and intensive health education (Sullivan, Hays, & Alexander, 2019). As such, interventions to improve self‐management are crucial (Powers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As such, interventions to improve self‐management are crucial (Powers et al, 2017). Health coaching has been shown to be an effective means of improving adherence to the diabetes treatment regimen, consequently improving glycemic control and reducing diabetes‐related complications (Huang, Chen, Chang, Su, & Lin, 2017; National Academies of Sciences, Engineering, & Medicine, 2017; Pirbaglou et al, 2018; Sherifali, Viscardi, Bai, & Ali, 2016; Sullivan et al, 2019; Wagner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%